Pengaruh Beauty Influencer Terhadap Keputusan Pembelian Produk Make Up Make Over Di Kota Bandung (Studi Kasus Tasya Farasya) - Nuraini, Anggi; Aulia, Pramitha (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Beauty Influencer is one way of marketing strategy in attracting consumers to make purchasing decisions for a product. The number of utilization of marketing methods using social media to reach and attract many consumers, one of which is by working with beauty influencers or beauty reviewers to promote these products. This study aims to determine the effect of beauty influencers on purchasing decisions on Make Over products. The research method applies a quantitative descriptive method, namely data obtained through a questionnaire. Nonprobability with purposive sampling was used as a sample method in these findings. The questionnaire was given to 100 respondents in Bandung City. The data analysis method used is simple linear regression analysis. From the results of the overall hypothesis test, beauty influencer Tasya Farasya partially has a significant effect on purchasing decisions for Make Over makeup products. This is evidenced by the value of tcount> ttable, namely 8.649> 1.660. Based on the coefficient of determination, beauty influencers have an influence of 43.3% on purchasing decisions for Make Over makeup products, while the remaining 56.7% has the influence of other variables not measured in these findings.